Characterization and formic acid oxidation studies of PtAu nanoparticles - Surin Saipanya (2018)
Copyright © 2014 American Scientific Publishers All rights reserved. Characterization and electrocatalytic oxidation of formic acid on PtAu nanoparticles supported multiwalled carbon nanotube (MWCNT) were studied. Electrochemical measurements were conducted in a self-made conventional three-electrode glass cell at room temperature. A Pt wire and Ag/AgCl were used as auxiliary and reference electrodes, respectively. The Pt was electrodeposited onto the electrode and their catalytic activities in the electrooxidation of formic acid were examined and compared. The morphology and composition were studied by a combination of transmission electron microscopy (TEM) and energy dispersive X-ray spectroscopy (EDX). Cyclic voltamograms of formic acid electrooxidation show a distinguishing shape with a prominent oxidation peak in the forward scan contributed to the formic acid oxidation whilst the backward scan is associated with the oxidation of exclusion of carbonaceous species. On the basis of the onset potential and current density, the resulting PtAu nanoparticles showed much higher electrocatalytic activity than other counterparts. The results show an excellent sign of applications for fuel cell.